2022
DOI: 10.3389/fphys.2022.1046204
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of reference genes for RT-qPCR-based analyses of Anastatus japonicus Ashmead (Hymenoptera: Helicopteridae)

Abstract: RT-qPCR remains a vital approach for molecular biology studies aimed at quantifying gene expression in a range of physiological or pathological settings. However, the use of appropriate reference genes is essential to attain meaningful RT-qPCR results. Anastatus japonicus Ashmead (Hymenoptera: Helicopteridae) is an important egg parasitoid wasp and natural enemy of fruit bugs and forest caterpillars. While recent transcriptomic studies have analyzed gene expression profiles in A. japonicus specimens, offering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Actin genes include ACT8 and ACT11, which we have long used as housekeeping genes [39]. In fact, under various diapause states and in different tissues, Anastatus japonicus [17] displayed that ACTIN was the most reliable, consistent with earlier findings on Locusta migratoria [40] and Spodoptera litura [41]. In this study, ACT expresses steadily in most cases.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Actin genes include ACT8 and ACT11, which we have long used as housekeeping genes [39]. In fact, under various diapause states and in different tissues, Anastatus japonicus [17] displayed that ACTIN was the most reliable, consistent with earlier findings on Locusta migratoria [40] and Spodoptera litura [41]. In this study, ACT expresses steadily in most cases.…”
Section: Discussionsupporting
confidence: 89%
“…RefFinder is a comprehensive evaluation tool that generates stability scores by estimating the geometric mean of internal control genes to lessen the effects of a single algorithm’s limitations [ 36 ]. Many species, including Neoceratitis asiatica [ 18 ] and Anastatus japonicus [ 17 ], were studied using a similar strategy. The expression of HSP90 under different temperature treatments was evaluated to authenticate our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies concerning the ORs and IRs of parasitoid wasps are essential for understanding the mechanisms of the olfactory system that finds the host pests and for developing an olfactory-based integrated pest management (IPM) strategy. Previous research on A. japonicus focused primarily on its morphology, ecology, and raising [ 1 , 5 , 6 , 7 , 9 , 35 , 36 , 37 ]; little information is available on its chemosensory mechanisms. Two previous studies have reported transcriptome datasets from female A. japonicus antennae [ 38 , 39 ], but neither of these studies involved the female abdominal and male antennal transcriptomes.…”
Section: Introductionmentioning
confidence: 99%